2022
DOI: 10.1093/nar/gkac077
|View full text |Cite
|
Sign up to set email alerts
|

H3K36 methylation and DNA-binding both promote Ioc4 recruitment and Isw1b remodeler function

Abstract: The Isw1b chromatin-remodeling complex is specifically recruited to gene bodies to help retain pre-existing histones during transcription by RNA polymerase II. Recruitment is dependent on H3K36 methylation and the Isw1b subunit Ioc4, which contains an N-terminal PWWP domain. Here, we present the crystal structure of the Ioc4-PWWP domain, including a detailed functional characterization of the domain on its own as well as in the context of full-length Ioc4 and the Isw1b remodeler. The Ioc4-PWWP domain preferent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…It was indicated that the molecular recognition between PTMs and chromatin-remodeling complex is required for nucleosome recruitment. Jian Li et al further reported the binding preference of the Ioc4-PWWP domain of Isw1b chromatin-remodeling complex with histone H3 lysine 36 tri-methylation (H3K36me3) and revealed the structural basis for the recognition [ 140 ]. Cynthia Tallant et al also reported the recognition preference of different domains of chromatin remodeling complex NoRC for different PTMs [ 141 ].…”
Section: The Crosstalk Of Multiple Factors and Effects On The High-or...mentioning
confidence: 99%
“…It was indicated that the molecular recognition between PTMs and chromatin-remodeling complex is required for nucleosome recruitment. Jian Li et al further reported the binding preference of the Ioc4-PWWP domain of Isw1b chromatin-remodeling complex with histone H3 lysine 36 tri-methylation (H3K36me3) and revealed the structural basis for the recognition [ 140 ]. Cynthia Tallant et al also reported the recognition preference of different domains of chromatin remodeling complex NoRC for different PTMs [ 141 ].…”
Section: The Crosstalk Of Multiple Factors and Effects On The High-or...mentioning
confidence: 99%
“…The methylation of H3K36, could regulate the activity of the Rpd3S complex to prevent nucleosome turnover [ 10 ]. Additionally, H3K36me3 enhances the affinity of the inhibitory Isw1b chromatin remodeling complex to nucleosome, resulting in a maintenance of chromatin constriction and reduction of chromatin accessibility [ 11 ]. Targeting the histone methyltransferase subunit EZH2, which has been found to be highly expressed in lung cancer, results in an increase in chromatin accessibility at regions marked by H3K27me3 [ 12 ].…”
Section: Introductionmentioning
confidence: 99%